A comparative study of the elastic properties of continuous tear curvilinear capsulorhexis versus capsulorhexis produced by radiofrequency endodiathermy. Issue 5 (May 1994) - Luck, J; Brahma, A K; Noble, B A
Abstract : Capsulorhexis using radio-frequency endodiathermy may confer some advantages over continuous tear curvilinear capsulorhexis (CTCC) in certain clinical situations. It is unclear whether a capsulorhexis produced in this fashion has the clinically advantageous elasticity and resistance to tearing that a CTCC has been demonstrated to have. To investigate this, a test of capsular elasticity was carried out on pairs of eyes obtained from an eye bank, 42 eyes of 21 patients in total, using modified digital vernier calipers. One eye of each pair had a CTCC, the other a diathermy capsulorhexis (DC). The elasticity of the capsule in both groups was expressed by comparing the circumference of the capsulotomy at rest with its circumference at rupture. The mean capsular elasticity of the CTCC group was significantly greater than that of the DC group (p << 0.001). The capsular edge in both groups was examined using scanning electron microscopy, and the difference in morphology appears to be the source of the difference in elasticity.